Hypothalamic response to kisspeptin and pituitary response to GnRH are preserved in healthy older men - Abbara,A; Narayanaswamy,S; Izzi-Engbeaya,C; Comninos,A; Clarke,S; Malik,Z; Papadopoulou,D; Coblentz,A; Sarang,Z; Bassett,P; Jayasena,C; Dhillo,W (Neuroendocrinology, 2018)
Background: Male testosterone levels decline by 1% per year from the age of 40yrs. Whilst a primary testicular deficit occurs, hypothalamic or pituitary dysregulation may also coexist. This study aimed to compare the hypothalamic response to kisspeptin and the pituitary response to GnRH of older men with those of young men. Methods: Following 1 hour of baseline sampling, healthy older men (n=5, mean age 59.3±2.9yrs) received a 3 hour intravenous infusion (IVI) of either: vehicle, kisspeptin-54 0.1, 0.3, 1.0nmol/kg/h, or GnRH 0.1nmol/kg/h on 5 different study days. Serum gonadotropins and total testosterone were measured every 10 minutes and compared to young men (n=5/group) (mean age 28.9±2.0yrs) with a similar BMI (24 kg/m2) who underwent the same protocol. Results: Kisspeptin and GnRH significantly stimulated serum gonadotropin release in older men compared to vehicle (P<0.001 for all groups). Gonadotropin response to kisspeptin was at least preserved in older men when compared with young men. At the highest dose of kisspeptin (1.0nmol/kg/h), a significantly greater LH (P=0.003) response was observed in older men. The FSH response to GnRH was increased in older men (P=0.002), but the LH response was similar (P=0.38). Serum testosterone rises following all doses of kisspeptin (P≤0.009) were reduced in older men. Conclusions: Our data suggests that healthy older men without late onset hypogonadism (LOH) have preserved hypothalamic response to kisspeptin and pituitary response to GnRH, but impaired testicular response. Further work is required to investigate the use of kisspeptin to identify hypothalamic deficits in men with LOH.